(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2010)
The characteristics of spinal block including ease of performance, efficacy, adverse effects and complications were evaluated in 78 children aged between 2-6 years undergoing different types of surgery in lower part of body. Spinal block was performed in sedated children with 0.5% hyperbaric bupivacaine at a dose of 0.25 mg/kg. Haemodynamically patients were stable in most of the cases. In general pulse rate was increased by 9.8% while systolic and diastolic blood pressures were reduced by 6.8% and 8.7% respectively from baseline level after 15 min of block, which didn’t warrant any active management. One patient was treated with injection atropine for bradycardia (<60 beats/min). Two patients had clinically significant hypotension (reduction of systolic blood pressure >20% from baseline level) and were easily managed with injection ephedrine hydrochloride. Two patients had insignificant sinus arrhythmia during operation and three required temporary supplemental oxygen support by mask to maintain oxygen salutation >94%. Motor block was complete in all but two cases. Sensory block showed wide variation of height, from first thoracic to seventh thoracic (4th thoracic). Time of two segment regression of block was 74 min (range 30-190 min). Mean time of giving rescue analgesic after spinal block was 118 min (range 59-240 min). One patient vomited and five had shivering in the recovery room. There was no incidence of systemic toxicity of bupivacaine (urinary retention, post dural puncture headache or any other neurological complication). Spinal block was observed to be easier, safer and very effective anaesthetic technique even in younger children. Key words: Spinal anaesthesia; children; complication. DOI: 10.3329/jafmc.v6i1.5988 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.25-28